Interactive Homework: A Tool for Parent Engagement - Laura Moore; Robert N. Ronau (Education Sciences, 2024)
Families have largely been excluded from the implementation of the Common Core State Standards in Mathematics (CCSSM), reducing their ability to extend their child’s mathematics learning. CCSSM emphasizes different instructional elements (e.g., pictorial representations, problem solving, multiple strategies for solving) that may differ greatly from how parents learned mathematics. In addition, many school officials have ineffectively engaged parents in the changes, further diminishing their capacity to participate in their child’s learning. This case study examined parent mathematics self-efficacy and parent mathematics knowledge for teaching, factors that influence the effectiveness of their engagement in their child’s mathematics learning. This study was also implemented to identify elements that the parent participant found helpful for their child’s mathematics learning. A thematic analysis was performed on the data sources, the interactive homework assignments, a survey, observations, a researcher’s journal, and an interview to conclude that the interactive homework assignments improved parent mathematics self-efficacy and parent mathematics knowledge for teaching. The parent participant also identified the assignments’ side-by-side examples, additional practice, and the easy access of the assignments as features of the intervention that enhanced her ability to support her child.